Liberal education in the University of the Philippines - Guerrero, Arturo M. 1911- (1954)
This study seeks to answer the following questions: (1) Does liberal education have a place in the scheme of instruction in the University of the Philippines? (2) If so, what is its concept of liberal education? (3) How does this concept stand in relation to recognized concepts of liberal education in the United States? (4) Is it properly implemented? (5) Are the curricula in the University designed to give the students the liberal education enunciated in the policies of the University?
Typewritten.
Vita.
Thesis (M.A.)--University of the Philippines, Diliman.
Keywords: Education, Humanistic